First record of a melanistic house sparrow "Passer domesticus" in India - Dilip Clinton, Samson Arockianathan; Ramakrishnan, Balasundaram; Samson, Arockianathan; Karthick, Sivaraj; Girikaran, Prabakaran; Deepan, Ravi (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
Melanism is a colour variation referring to the excessive deposition of the pigment melanin, resulting in feathers darker than normal. Two classes of melanin are distinguished: eumelanins are responsible for black feathers while phaeomelanins are responsible for a range of brown feathers (Jawor and Breitwisch 2003, McGraw 2006).
Keywords: wróblowe; ornitologia